The Power of Dung : Lessons Learned from On-Farm Biodigester Programs in Africa - World Bank (World Bank, Washington, DC, 2019)
Over half the world’s population cooks primarily with wood, charcoal, coal, crop waste, or dung. This share is currently increasing or stagnant in most regions. Dependence on solid fuels is one of the world’s major public health challenges, causing more premature deaths than HIV/AIDS, malaria, and tuberculosis combined. The use of solid fuels and stoves also imposes significant economic costs on societies that can least afford them and contributes to adverse environmental and climate change effects. Traditionally the area of improving access to modern energy services has fallen in the realm of energy experts. However, a new study conducted by the World Bank between 2017-2019 asks the question: Does Agriculture have a role to plan in improving access to modern cooking services? The report: “The Power of Dung: Lessons Learned from On-Farm Biodigester Programs in Africa” examines on-farm biodigester programs in selected countries in Africa and examines the success factors of the programs. One of the report’s most important findings is that reframing the promotion of biodigesters from one providing clean cooking solutions (energy) to one providing improved fertilizers (agriculture) increases the attractiveness of the solutions among farmers.